Traumatic memory and the abuse of child rights in Things Fall Apart - Onuoha, Onyekachi Peter (Pedagogika Społeczna Nova, 2022)
Neglect is a form of child abuse it is the failure of parents to redeem their obligation towards their children. In the novel titled: Things Fall Apart (henceforth TFA) written by Chinua Achebe, the protago- nist called Okonkwo suffers parental neglect, which of course led to his ultimate downfall. Okonkwo’s father, Unoka failed to give adequate parental care to his son as portrayed by Achebe in the novel and that parental gap acted as an inertia in Okonkwo’s tragic end. Through the application of trauma theory, this study examines childhood trauma and how it conditions the character in adulthood in African novel. The study adopts the discursive approach to textual analysis and observes that toxic masculinity is a product of poor parenting resulting in childhood traumatic experiences that culminate into the use of force, exploitation and victimization cum abuse of children and women as depicted in TFA. The study submits that Okonkwo’s childhood trauma in TFA is an unexplored fear that influences and conditions him even unto adulthood. This study opines that Okonkwo’s trauma is a site for extended traumatization of kin and that Okonkwo’s unhealed trauma finds expression in his survival antics. The study concludes that Okonkwo is a trauma patient and his success and failure in Umuofia is a product of trauma.